Concepts of progress and the construction of a national project: towards a history of ideas in Mexico’s extended 19th century (1821-1910) - Enríquez Pérez, Isaac (2019)
The present article seeks to go beyond the well-worn, one-dimensional labels that divided nineteenth century societies of the independence period, providing instead an overview of the concepts of progress that spread through Mexico between 1821 and 1910, emphasizing the reception, re-elaboration, dissemination and public impact of this notion, not without briefly analyzing the economic history of the period and the effects of the policies inspired by them. The text traces the positions and stances of various thinkers and ideologists vis-à-vis the role and functions of the State in the construction of markets and distribution of wealth, seeking an archeology of thought that gets to the bottom of the transformation of the history of Mexican ideas exposed to the heat of the convolutions of the nineteenth and early twentieth century, while successfully shaping the identity of the nation-state and laying the foundations of capitalism on the basis of the influence of various trends of liberalism and the institutional framework inspired by this ideology.